Preventing Cerebral Oedema in Acute Liver Failure: The Case for Quadruple-H Therapy. Issue 1 (January 2014) - Warrillow, S. J.; Bellomo, R.
Severe cerebral oedema is a life-threatening complication of acute liver failure. Hyperammonaemia and cerebral hyperaemia are major contributing factors. A multimodal approach, which incorporates hyperventilation, haemodiafiltration, hypernatraemia and hypothermia (quadruple-H therapy), may prevent or attenuate severe cerebral oedema. This approach is readily administered by critical care clinicians and is likely to be more effective than the use of single therapies. Targeting of PaCO2 in the mild hyperventilation range, as seen in acute liver failure patients before intubation, aims to minimise hyperaemic cerebral oedema. Haemodiafiltration aims to achieve the rapid control of elevated blood ammonia concentrations by its removal and to reduce production via the lowering of core temperature. The administration of concentrated saline increases serum tonicity and further reduces cerebral swelling. In addition, the pathologically increased cerebral blood-flow is further attenuated by therapeutic hypothermia. The combination of all four treatments in a multimodal approach may be a safe and effective means of attenuating or treating the cerebral oedema of acute liver failure and preventing death from neurological complications.